Enforceability of Arbitration Awards and Jurisdictional Uncertainty: A Study of Kompetenz-Kompetenz and Party Autonomy in PCA Case No. 2015-40 - Marilyn, Sharon; P. Soemartono, Gatot (Dinasti Research, 2024)
Ideally, arbitration is an alternative dispute resolution that frequently applies in subjects of international commerce. In fact, it is the determination of an issue without resorting to the court. The very first issue of concern that needs to be established in adjudicating any matter of arbitration is jurisdiction. Without doing so, no question of a substantive issue of a case can be addressed. In this case, several issues regarding jurisdiction came into question in the PCA case No. 2015-40 involving IMFA and The Republic of Indonesia. Thus, while the jurisdictional objections filed by the respondent were unanswered, the tribunal advanced and addressed the merits of the case. It was after filing its reply; therefore, this paper shall research the effect of such jurisdictional ambiguities on the enforceability of an award.The method in this paper is qualitative, based on existing literature, the principles of party autonomy, and kompetenz-kompetenz. The contention is that although technically possible to retain jurisdiction, it is not advisable to overlook such jurisdictional objections simply because the outcome is ambiguous and one sets a bad precedent.